Dynamic Response of Idiopathic Scoliosis and Kyphosis Spine - Li, Pengju; Fu, Rongchang; Yang, Xiaozheng; Wang, Kun (Shanghai jiao tong da xue xue bao, 2025)
The dynamic response characteristics of scoliosis and kyphosis to vibration are currently unclear. The finite element method (FEM) was employed to study the vibration response of patients with idiopathic scoliosis and kyphosis. The objective is to analyze the dynamic characteristics of idiopathic scoliosis and kyphosis using FEM. The finite element model of T1—S1 segment was established and verified using the CT scanning images. The established scoliosis and kyphosis models were verified statistically and dynamically. The finite element software Abaqus was utilized to analyze the mode, harmonic response, and transient dynamics of scoliosis and kyphosis. The first four natural frequencies extracted from modal analysis were 1.34, 2.26, 4.49 and 17.69 Hz respectively. Notably, the first three natural frequencies decreased with the increase of upper body mass. In harmonic response analysis, the frequency corresponding to the maximum amplitude in x direction was the first order natural frequency, and the frequency corresponding to the maximum amplitude in y and z directions was the second order natural frequency. At the same resonance frequency, the amplitude of the thoracic spine was larger relative to that of the lumbar spine. The time domain results of transient analysis showed that the displacement dynamic response of each segment presented cyclic response characteristics over time. Under 2.26 Hz excitation, the dynamic response of the research object appeared as resonance. The higher the degree of spinal deformity, the greater the fundamental frequency. The first three natural modes of scoliosis and kyphosis contain vibration components in the vertical direction. The second order natural frequency was the most harmful to patients with scoliosis and kyphosis. Under cyclic loading, the deformation of the thoracic cone exceeds that of the lumbar cone.